2013
DOI: 10.1159/000356825
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Reactive Amyloidosis Associated with Castleman's Disease

Abstract: We report this case of secondary amyloidosis associated with Castleman's disease. A 51-year-old man presented with systemic symptoms of generalized weakness, fatigue, unintended weight loss, anorexia and progressively worsening abdominal distension. On examination he was found to have an indurated right-sided submandibular mass and tense ascites. He was found to have multiorgan dysfunction with deranged liver function tests and renal failure. Ascitic fluid analysis revealed evidence of spontaneous bacterial pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
0
7
0
2
Order By: Relevance
“…The rarity of the disease also influences the therapeutic approach, no unique therapeutic regimens being unanimously accepted [ 3 , 9 , 10 , 11 , 12 ]. Disease associations include the POEMS syndrome (Polyneuropathy, Organomegaly, Endocrinopathy, M-protein, and Skin changes) [ 13 , 14 ], Kaposi sarcoma, pemphigus, refractory anemia, nephrotic syndrome, amyloidosis [ 15 , 16 , 17 ]. Associations with lymphoid malignancies have been described and these include: diffuse large- B cell lymphoma, mantle cell lymphoma, peripheral T-cell lymphoma and lymphoplasmacytic lymphoma, follicular lymphoma [ 18 ].…”
Section: Background and Aimsmentioning
confidence: 99%
“…The rarity of the disease also influences the therapeutic approach, no unique therapeutic regimens being unanimously accepted [ 3 , 9 , 10 , 11 , 12 ]. Disease associations include the POEMS syndrome (Polyneuropathy, Organomegaly, Endocrinopathy, M-protein, and Skin changes) [ 13 , 14 ], Kaposi sarcoma, pemphigus, refractory anemia, nephrotic syndrome, amyloidosis [ 15 , 16 , 17 ]. Associations with lymphoid malignancies have been described and these include: diffuse large- B cell lymphoma, mantle cell lymphoma, peripheral T-cell lymphoma and lymphoplasmacytic lymphoma, follicular lymphoma [ 18 ].…”
Section: Background and Aimsmentioning
confidence: 99%
“…The relationship between CD and secondary amyloidosis was reported before, and most cases revealed amyloid deposits in kidney. [69] Secondary amyloidosis is believed to be caused mainly by chronic inflammation, and large amounts of IL-6 produced in the germinal center of CD may enhance the production of precursor of amyloid. [10,11]…”
Section: Discussionmentioning
confidence: 99%
“…9,10 More than 50 reports of amyloidosis associated with CD have been published thus far in the medical scientific literature including hepatic amyloid deposition. [11][12][13][14][15] Of note, Morita-Hoshi, et al 11 reviewed 45 cases of systemic amyloidosis related to CD and showed that:…”
Section: Discussionmentioning
confidence: 99%